2015
DOI: 10.1177/0271678x15606455
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic fMRI in the mouse hippocampus: Hemodynamic response to brief glutamatergic stimuli

Abstract: The combination of optogenetics with functional magnetic resonance imaging is a promising tool to study the causal relationship between specific neuronal populations and global brain activity. We employed this technique to study the brain response to recruitment of glutamatergic neurons in the mouse hippocampus. The light-sensitive protein channelrhodopsin-2 was expressed in a-CamKII-positive glutamatergic neurons in the left hippocampus (N ¼ 10). Functional magnetic resonance imaging was performed during loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…This more complete memory impairment suggests that the abnormal activity patterns induced by ChR2 stimulation disrupted encoding in brain regions that can normally compensate for the loss of the dorsal hippocampus. Consistent with this idea, stimulation of dCA1 has been shown to produce widespread increases in brain activity (Takata et al, 2015; Lebhardt et al, 2016). In contrast to our results, some studies have found that increases in CA1 activity during encoding enhance trace fear memory acquisition (Kitamura et al, 2014; Sellami et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…This more complete memory impairment suggests that the abnormal activity patterns induced by ChR2 stimulation disrupted encoding in brain regions that can normally compensate for the loss of the dorsal hippocampus. Consistent with this idea, stimulation of dCA1 has been shown to produce widespread increases in brain activity (Takata et al, 2015; Lebhardt et al, 2016). In contrast to our results, some studies have found that increases in CA1 activity during encoding enhance trace fear memory acquisition (Kitamura et al, 2014; Sellami et al, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…Upon preprocessing (see Methods section and Fig. S2A-C ), we computed a general linear model (GLM) on the BOLD time series of the 51 sessions, modeling CS and US timepoints as events, which were parametrically modulated as described below, and convolved with a previously determined mouse hemodynamic response function (Lebhardt et al, 2016). When parametrically modulating the CS regressor with the model-estimated RP value at CS, V ( CS ), we observed broad recruitment of brain regions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned, the HRF varies significantly between species, with faster kinetics in mice compared to humans (Chen et al, 2020, Lebhardt et al, 2016, Schlegel et al, 2015). We therefore used a mouse-specific HRF estimated by Lebhardt et al, 2016. In all models, CS and US timepoints were modelled as events (“stick functions”, duration 0 s).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Lebhardt et al. 104 unilaterally applied optogenetic stimulation to the hippocampus of CaMKIIα-Cre mice and found that glutamatergic neuron activity in the hippocampus (dependent on where along the dorso-ventral axis) led to a significant positive BOLD response, bilaterally at the site of stimulation, frontal lobe, and septum; ipsilaterally in the nucleus accumbens (NAc); and contralaterally in the striatum. Opto-fMRI of the ventrolateral orbitofrontal cortex (VLO) showed that this area also exhibits a global influence on brain activity.…”
Section: Recent Advances and Applicationsmentioning
confidence: 99%